Kegiatan knowledge sharing pada literasi finansial di Komunitas Finansialku - Sultan Aulia; Yunus Winoto; Rully Khairul Anwar (Faculty of Communication, Padjadjaran University, 2023)
The millennial generation is susceptible consumptive lifestyle. Finansialku Community help millennial generation to improve financial literacy through finance and investment management. The purpose this research to know how knowledge sharing activity in financial literacy at Finansialku Community. The research method was qualitative through case study approach. Based on research result, Finansialku Community have two of knowledge sharing consist of Teletalks and Ngobrolsore. Teletalks is knowledge sharing activity using text chat medium and Ngobrolsore is activity used voices, like Webinar and became a preference to members to learn by listening to knowledge. Knowledge sharing in the community through fourth stage, consist of socialization, externalization, combination, and internalization. Members in socialization stage interact to each other, and share knowledge and experience. Members in externalization stage articulated knowledge in explicit shape. Members have combined many knowledge that externalized in combination stage to create comprehensive and holistic the new knowledge. Members have applied combination knowledge in daily life that members can increase finance literacy. Finansialku Community succeed to increase financial literacy to members. Members of Finansialku Community can increase their skills and they have competence in finance management in the personal, family, and environment stage. Finansialku Community in knowledge sharing have been helping members to increase financial literacy through the best and effective finance management. Therefore, knowledge sharing activity in Finansialku Community is one solutions to increase finance literacy in public.